Medication use in the last year of life: a cross-sectional hospice study. Issue Volume 12:Issue e6(2022) (11th August 2020) - Scullion, Liam; Dodds, Hope; Liu, Qinghao; Hunt, Mary Elizabeth; Gordon, Simon; Todd, Adam
Abstract : Objectives: The issue of polypharmacy and medication use in people with life limiting illness raises important questions from a clinical and ethical viewpoint. The objectives of our study were to (1) explore medication use among people with life limiting illness receiving hospice care; (2) apply consensus criteria to assess medication appropriateness; and (3) determine the overall pill burden in this patient population. Methods: Six hospices in the North East of England were included. All deceased adult patients who received hospice care in 2018 were eligible for study inclusion. Descriptive statistics were used to report medication details; while medication appropriateness was assessed according to consensus criteria developed by Morin and colleagues. Results: Six hundred and ninety patients were included in the study. Patients were using a mean number of 8.8 medications per day, while polypharmacy was evident in 80% of patients. In terms of potentially questionable medication, patients were prescribed a mean number of 1.3 per day. Common potentially questionable medications included vitamin and mineral supplements, antihypertensives, antiplatelets, lipid regulating agents and anticoagulants. The pill burden in this population was also high with, on average, people using 13.7 oral doses per day. Conclusions: Polypharmacy is common in patients accessing hospice care, as is the use of potentially questionable medication. The pill burden in this patient population is also high, which may be an additional treatment burden to patients. Holistic deprescribing approaches for this population should be developed and implemented.